Telaah Kritis terhadap Materialitas Ilmu dalam Perspektif Filsafat Teknologi Don Ihde - Nela Suci Rahmatillah (Jurnal Riset Agama, 2022)
This research aims to discuss the instruments of science and the materiality of science in the perspective of technology philosophy Don Ihde. This research method is qualitative through library research. Therefore, this research focuses its study on sources that are literate without the need for field research. The results and discussion include scientific analysis through material hermeneutics according to Don Ihde's thinking. The findings of this study based on Don Ihde's view, it can be understood that science is hermeneutics because science is an attempt to interpret by understanding phenomena through the senses or in another meaning such as giving meaning to writing in a text. While reading the materiality of science is not only limited to connected phenomena. The materiality of science includes the rationality of technologically structured instruments. This allows the reading of the world not to be perceived by the senses. Therefore, reading the materiality of science is always accompanied by reading the materiality of technology.